Athanasius and the Holy Spirit : the development of his early pneumatology - Hill, Kevin Douglas (Minneapolis : Fortress Press, 2016)
Most studies of Athanasius on the Holy Spirit have concentrated on his Letters to Serapio on the Holy Spirit. In this book, Kevin Douglas Hill looks at his earlier writing and argues that without that earlier work he would not have been prepared to confess the Holy Spirit's divine nature and role in creating the world. 600 00 Athanasius,|cSaint, Patriarch of Alexandria,|d-373.
Part I. Athanasius's pastoral works. 1. The problem of pneumatological reticence in Against the Pagans-On the incarnation -- 2. Pneumatology in the early pastoral work -- 3. Pneumatology in the later pastoral works -- Part II. The Orations against the Arians. 4. A foundational pneumatology: the Holy Spirit in Athanasius's Trinitarian arguments -- 5. Essential for salvation: Psalm 45:7 and Christ's reception of the Holy Spirit -- 7. The spirit of the Son: the Holy Spirit's union with the Son.
Includes bibliographical references (pages 265-284) and index.
Keywords: Theology, Doctrinal; Theology; Holy Spirit -- History of doctrines